Eco-Business Diplomacy: A Case Study of SMART and the European Union on Palm Oil Issue - Robertua, Verdinand; Bayu Sontany, Raden Ariobimo (Department of International Relations Universitas Pertamina, 2021)
The European Union imposed tougher policy to Indonesia on palm oil trade due to sustainability issues. PT Smart Tbk is one of the biggest palm oil company in Indonesia. Due to the trade conflict between the European Union and Indonesia, PT Smart Tbk played its role in eco-business diplomacy. This research used primary data by interviewing representatives from PT Smart Tbk. The authors proposed the concept of eco-business diplomacy by combining the concept of environmental diplomacy and business diplomacy using the case study of PT Smart Tbk’s relationship with the European Union.